Altered Circulating Cell-free Mitochondrial DNA of Patients with Congenital Scoliosis. Issue 8 (15th April 2021) - Yang, Guanteng; Tang, Mingxing; Zhang, Hongqi; Li, Jiong; Xiao, Lige; Guo, Chaofeng
Abstract : Study Design: Case–control study. Objective: The aim of this study was to estimate the relationship between circulating cell-free DNA (ccf DNA) and clinical parameters of patients with congenital scoliosis (CS). Summary of Background Data: CS is a complex spinal deformity characteristic of congenital vertebral malformations. Although numerous studies have centered on the etiology of CS, the cause of CS remains unclear. Previously, we reported that circulating cell-free DNA (ccf DNA) is altered in adolescent idiopathic scoliosis ( AIS). However, the relationship between ccf DNA and the clinical parameters of patients with CS remains unclear. Methods: The plasma of peripheral blood from 35 patients with CS and 32 age-matched controls was collected for ccf DNA analysis. Quantitative PCR was used to detect ccf n-DNA and ccf mt-DNA levels, and correlation analyses between ccf n-DNA and ccf mt-DNA levels were conducted. Receiver-operating characteristic (ROC) curves were used to analyze the sensitivity and specificity of ccf n-DNA and ccf mt-DNA levels to different characteristics. Results: The plasma ccf mt-DNA levels of both ND1 and CYTC were significantly decreased in patients with CS compared with levels in controls both in total and by sex, whereas the plasma ccf n-DNA levels showed no significant difference. There is no difference in both ccf mt-DNA and ccf n-DNA between S-SDV and M-SDV according to The International Consortium for Vertebral Anomalies and Scoliosis (ICVAS) classification. The ROC curve analyses showed a reliable sensitivity and specificity of CS predicted by ccf mt-DNA levels in total but failed to distinguish different ICVAS types. Conclusion: Significantly decreased plasma ccf mt-DNA levels were observed in patients with CS compared with those in controls. Although this finding has limited significance for clinical practice, it indicates that ccf mt-DNA may predict the onset or development of CS. Further studies should focus on the role of ccf mt-DNA in embryo development and whether ccf mt-DNAs could be considered as a marker for prenatal screening in development disorder like CS. Level of Evidence: 4 Abstract : Supplemental Digital Content is available in the textThe concentration of plasma ccf mt-DNA in congenital scoliosis (CS) was significantly lower than controls. Although the ROC curve analysis shows no prediction regarding sex and The International Consortium for Vertebral Anomalies and Scoliosis types, the alteration of ccf mt-DNA may be involved in the onset or development of CS.